Current vs Time Curve Analysis for the Anodic Preparation of Titania Nanotube Arrays. (1st January 2015) - Cao, Chunbin; Zhang, Guoshun; Ye, Jian; Hua, Rimao; Sun, Zhaoqi; Cui, Jingbiao
Abstract : Highly ordered TiO2 nanotube arrays (TNAs) were electrochemically anodized in NH4 F dissolved glycerol based electrolytes with various deionized water concentrations. Electrode current data under various water concentrations in the electrolytes and the corresponding nanontube growth were analyzed in details. The current change during deposition was found to correlate well with the morphology and structure of the TNAs, including tube wall thickness, tube spacing, ridge distribution, inner tube diameter, and tube length. The water concentration in the electrolytes plays a key role in regulating the current during deposition though a typical three-stage growth is seen in cases with lower water concentration. The higher water concentrations cause the duration of each growth stage to be shorter, which is more complicated than the typical three-stage growth model and exhibits different structures of the initial barrier oxide and resulted TNAs. Current oscillation was also observed, which corresponds to the growth ridges along the nanotubes. This study suggests that real time control of the nanotube growth may be achievable by monitoring the detailed current curve during deposition.